Students' Perception of Class XII Fashion Design at SMK An-Nur Al Munir on Speaking Skills - Ali, Muhammad (International Journal of Language Teaching and Education, 2022)
Education is instrumental in shaping the lives of individuals in a society. Educational institutions need to provide quality education to prepare the students for the future generation. As such, schools offer an environment where students can learn the required skills and knowledge. Every organization has different characteristics based on its purpose and mission. All students have varied perspectives on what it means to learn to speak English, according to students' perceptions. The purpose of this study is (1) describe Students’ Perception Toward Speaking Skills at An-Nur Al Munir Vocational High School. The focus of this study is qualitative analysis. The researcher used a descriptive qualitative research approach as a design strategy because it was analogous to gathering information from students' perceptions. The use of this research approach is tailored to the basic purpose of research, namely to describe twelfth-grade students’ perception of English-speaking lessons at An-Nur Al Munir Vocational High School. The results of Students’ Perception Toward Speaking Skill at An-Nur Al Munir Vocational High School show that Facilities that support learning activities well, including this English-speaking learning activity, result in enjoyable learning. Various students have different opinions about language acquisition. Some come with a lot of benefits, while others have some drawbacks. However, the researcher's data show that An-Nur Al-Munir Vocational High Schools twelfth-grade fashion students who are learning to speak English have more advantages than disadvantages in doing so.